Non-alcoholic fatty liver disease and incident major adverse cardiovascular events: results from a nationwide histology cohort. Issue 9 (6th September 2021) - Simon, Tracey G; Roelstraete, Bjorn; Hagström, Hannes; Sundström, Johan; Ludvigsson, Jonas F
Abstract : Objective: Some data suggest a positive association between non-alcoholic fatty liver disease (NAFLD) and incident major adverse cardiovascular events (MACEs). However, data are lacking from large cohorts with liver histology, which remains the gold standard for staging NAFLD severity. Design: This population-based cohort included all Swedish adults with histologically confirmed NAFLD and without cardiovascular disease (CVD) at baseline (1966–2016, n=10 422). NAFLD was defined from prospectively recorded histopathology and categorised as simple steatosis, non-fibrotic steatohepatitis, non-cirrhotic fibrosis and cirrhosis. Patients with NAFLD were matched to ≤5 population controls without NAFLD or CVD, by age, sex, calendar year and county (n=46 517). Using Cox proportional hazards modelling, we calculated multivariable adjusted HRs (aHRs) and 95% CIs for MACE outcomes (ie, ischaemic heart disease (IHD), stroke, congestive heart failure (CHF) or cardiovascular (CV) mortality). Results: Over a median of 13.6 years, incident MACE was confirmed in 2850 patients with NAFLD and 10 648 controls. Patients with NAFLD had higher incidence of MACE than controls (24.3 vs 16.0/1000 person-years (PY); difference=8.3/1000 PY; aHR 1.63, 95% CI 1.56 to 1.70), including higher rates of IHD (difference=4.2/1000 PY; aHR 1.64, 95% CI 1.54 to 1.75), CHF (difference=3.3/1000 PY; aHR 1.75, 95% CI 1.63 to 1.87), stroke (difference=2.4/1000 PY; aHR 1.58, 95% CI 1.46 to 1.71) and CV mortality (difference=1.2/1000 PY; aHR 1.37, 95% CI 1.27 to 1.48). Rates of incident MACE increased progressively with worsening NAFLD severity (ptrend =0.02), with the highest incidence observed with cirrhosis (difference vs controls=27.2/1000 PY; aHR 2.15, 95% CI 1.77 to 2.61). Conclusion: Compared with matched population controls, patients with biopsy-proven NAFLD had significantly higher incidence of MACE, including IHD, stroke, CHF and CV mortality. Excess risk was evident across all stages of NAFLD and increased with worsening disease severity.